Perbandingan Latihan Push-up With Band Dengan Bench Press With Band Terhadap Peningkatan Daya Tahan Otot Lengan - Ginanjar, Tantan Satia; Sugiawardana, Ruli; Hartono, Tony (Jurnal Keolahragaan, 2022)
The purpose of the study was to determine the effect of push-up with band exercise with bench press with band on increasing arm muscle endurance (ME). the method used is pre-experimental. The research design is a two group pretest-posttest design. The population of this study were male students of SMA Negeri 2 Ciamis Regency totaling 30 male students. The technique of using the sample uses total sampling. The research instrument used was a push up test. The results of the study were that there was a significant effect of push ups with band exercises on increasing arm ME in SMA Negeri 2 Ciamis Regency students. There is a significant difference between push-up exercises with bands and bench press with bands on increasing arm ME in SMA Negeri 2 Ciamis Regency students. The conclusion of the research: Push-up exercise with band has a significant effect on increasing the ME arm in grade 2 students of SMA Negeri 2 Ciamis Regency. The bench press with band exercise has a significant effect on increasing the ME arm in grade 2 students of SMA Negeri 2 Ciamis Regency. There is a significant difference between push-up exercises with bands and bench presses with bands on the increase in arm ME in grade 2 students of SMA Negeri 2 Ciamis Regency. Suggestion: It is hoped that other researchers can find weaknesses that can improve research on the form of push-up exercises with bands and bench presses with bands on increasing arm muscle endurance.Tujuan penelitian untuk mengetahui pengaruh latihan push-up with band dengan bench press with band terhadap peningkatan muscle endurance (ME) lengan. metode yang digunakan pre eksperimen. Desain penelitian yaitu two group pretest-posttest design. Populasi penelitian ini adalah siswa putra SMA Negeri 2 Kabupaten Ciamis berjumlah 30 siswa putra. Teknik penggunaan sampel menggunakan total sampling. Instrumen penelitian yang digunakan yaitu tes push up. Hasil penelitian yaitu ada pengaruh yang signifikan latihan push up with band terhadap peningkatan ME lengan pada siswa SMA Negeri 2 Kabupaten Ciamis..Ada pengaruh yang signifikan latihan bench press with band terhadap peningkatan ME lengan pada siswa SMA Negeri 2 Kabupaten Ciamis..Ada perbedaan secara signifikan antara latihan push-up with band dengan bench press with band terhadap peningkatan ME lengan  pada siswa SMA Negeri 2 Kabupaten Ciamis. Kesimpulan hasil penelitian: Latihan push-up with band memberikan pengaruh yang signifikan terhadap peningkatan ME lengan pada siswa kelas 2 SMA Negeri 2 Kabupaten Ciamis. Latihan bench press with band memberikan pengaruh yang signifikan terhadap peningkatan ME lengan pada siswa kelas 2 SMA Negeri 2 Kabupaten Ciamis. Ada perbedaan secara signifikan antara latihan push-up with band dan bench press with band terhadap peningkatan ME lengan pada siswa kelas 2 SMA Negeri 2 Kabupaten Ciamis. Saran: Diharapkan bagi peneliti lain dapat menemukan kelemahan-kelemahan yang mampu menyempurnakan penelitian bentuk latihan push-up with band dan bench press with band terhadap peningkatan daya tahan otot lengan.